Antibiotics from predatory bacteria - Korp, Juliane; Vela Gurovic, María S.; Nett, Markus (Beilstein Journal of Organic Chemistry, 2016)
Bacteria, which prey on other microorganisms, are commonly found in the environment. While some of these organisms act as solitary hunters, others band together in large consortia before they attack their prey. Anecdotal reports suggest that bacteria practicing such a wolfpack strategy utilize antibiotics as predatory weapons. Consistent with this hypothesis, genome sequencing revealed that these micropredators possess impressive capacities for natural product biosynthesis. Here, we will present the results from recent chemical investigations of this bacterial group, compare the biosynthetic potential with that of non-predatory bacteria and discuss the link between predation and secondary metabolism.
Keywords: antibiotics; genome mining; Herpetosiphon; myxobacteria; predation